Decline or redeployment? The sociology of work in the UK - Carol Stephenson; Paul Stewart (La Nouvelle Revue du Travail)
This paper takes issue with previous influential accounts of the evolution and contemporary potency of the Sociology of work (SoW) in the UK by challenging mythologies which have grown up around the trajectory of the sub-discipline. This paper is based on a sociological analysis of the political, organisational and social forces which have shaped the sub-discipline and comprehensive examination of its broad and complex canon. This enables a refutation of previous orthodoxies which suggest that a clearly defined SoW previously existed in, and emerged from, the narrow confines of Sociology departments only, and relatedly, that a ‘Golden Age’ of SoW research existed in the post WW II era and that its ending led to the irrevocable decline of the sub-discipline. These misinterpretations are politically problematic in that they laud an era of research which neglected complex and important questions in relation to who holds power and how that is exercised and in relation to the reproduction of social inequality within work and employment and furthermore, are based on a narrow interpretation of the SoW. This paper overturns conventional wisdom about the contemporary importance and relevance of the sub-discipline: where others have identified decline we explore SoW’s relationship to power and inequality and the spread and breath of its impact and concludes that the spread of discipline beyond the narrow confines of academia offers opportunities for radical social change.